Expression Trend of Selected Ribosomal Protein Genes in Nasopharyngeal Carcinoma - Sim, Edmund; Ling, Teck Yee; Tiong, Thung-Sing; Selva, Subramaniam; Khoo, Alan (My Jurnal, 2012)
Ribosomal proteins are traditionally associated with protein biosynthesis until recent studies that implicated their extraribosomal functions in human diseases and cancers. Our previous studies using GeneFishingTM DEG method and microarray revealed underexpression of three ribosomal protein genes, RPS26, RPS27, and RPL32 in cancer of the nasopharynx. Herein, we investigated the expression pattern and nucleotide sequence integrity of these genes in nasopharyngeal carcinoma to further delineate their involvement in tumourigenesis. The relationship of expression level with clinicopathologic factors was also statistically studied.